Technical and economic aspects of low emission reduction in Poland - Dzikuć, Maciej; Dzikuć, Maria; Łasiński, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents the problem of excessive air pollution in Poland caused mainly by low emission. The emission arises in result of heating flats by means of old and energetically inefficient heating installations. In Poland and Bulgaria the inhaled air is of the worst quality out of all EU countries. The paper presents economic and technical problems related to low emission occurring during the combustion of solid fuels in local boiler houses. Furthermore, the most significant economic issues, connected with the reduction of low emission are discussed, as well as technological possibilities of efficient reduction of the amount of pollution in the atmosphere. Conclusions are presented at the end of the article.
Keywords: economy; energy; ecology; low emissions